Effect of different levels of biogas manure in the growth and development of cultivated potato crop in Tartous governorate (Damascus University Journal of agriculture sciences, 2021)
The research was carried out at the Center for Agricultural Scientific Research, in Tartous, on potato (cult. Spunta) in spring season 2017 to investigate the effect of fertilization levels on the growth and development of potato plant. The experiment included four experimental treatments consisting of control (without fertilization) and three levels of biogas manure (B) (4,8,12 m3/d ). The Block Randomized design was adopted with  three replicates for each treatment, and at the rate of 30 plants per replicate.The results of the study showed a positive effect for the addition of biogas manure on improving the growth of potato plant. There was an increase in all growth indicators with increased rates of addition of manure. Treatment (B3) gave the highest value for all indicators .plant height (36.81 cm), number of stems / plant (2.93 stems / plant), number of leaves (13.17) leaves / plants), leaf surface area (2331 cm2), leaf surface index (1.4),while  wet and dry weight of the plant (92 ,12 g)respectively.
Keywords: Biogas manure; Potato